John Dos Passos. - Davis, Robert Gorham (University of Minnesota pamphlets on American writers ;, 1962)
John Dos Passos - American Writers 20 was first published in 1962. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.